MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA MELALUI PENERAPAN MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) - Kusumawardani, Siska (Jurnal Holistika, 2017)
The Implementation Of Cooperatif Learning Model, Type Teams Games Tournament (TGT) IN EFFORTS To Improve the Mathematical Comprehension Ability For Studentsd Of Fifth Grade At Madrasah Ibtidai- yah. The learning process on MIN 1 Class V in Bandung executed tend passive, where concepts obtained still used teacher centered. So we needed to seek alternative learning to be able to improve student math- ematical comprehenshion. Cooperative Learning Model Type TGT is one alternative that can be used in efforts to improve students mathematical comprehension will increase. This research conducted also for knowing the improvement of student mathematical comprehension ability after implementation Coopera- tive Learning Model types TGT on Geometry and Measurement. After conducted in six-time meeting, the results showed that the students and teacher activites in learning mathematics using Model Cooperative learning model type TGT accomplished